PROBLEMATICS OF ONLINE GAMBLING IN INDONESIA Structural Da'wah Approach - Fatuh Widoyo, Agus; mastori; Arifin, Zenal (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
ABSTRACT Based on the latest data reported by the media, online gambling transactions have entered a very disturbing stage. How could it not be, the transaction figures reach hundreds of trillions and involve students, housewives, people and officials. As a result, hereditary problems emerge that endanger society, such as divorce, suicide and murder. Various efforts have been made to tackle the rise of gambling, especially online gambling. Such as oral bill preaching, education and eradicating gambling sites. However, online gambling actually shows that the trend is increasing and increasing. On that basis, the main topic of this article discusses the structural da'wah perspective in comprehensively eradicating online gambling. The aim of this research is to analyze the phenomenon of online gambling and its solutions within the structural da'wah paradigm. This research uses qualitative methods using library data such as books, journals and online news sites that have been verified and related to the research object. The results of this research reveal that structural da'wah can be an essential solution to eradicating online gambling. Because the structural position of the government has the power and strength to order and prohibit in accordance with the principles of da'wah. Keywords: problems, online gambling, da'wah, structural